Transferable Drug Resistance Among Enterobacteriaceae Isolated from Human Urinary Tract Infections - Sieckmann, Donna G. (1969)
Fifteen sulfonamide-resistant cultures isolated from urinary tract infections in eastern Nebraska were screened for transferable drug resistance by three methods. Seven of the 15 resistant cultures could transfer resistance of varying levels to two or more chemotherapeutic agents. Transfer of drug resistance occurred without accompanying transfer of chromosomal traits and required cell to cell contact. In mixed culture, the number of drug-resistant recipients increased exponentially, reaching a plateau 2 hr after mixing. Spontaneous or artificial elimination of resistance was found to be a rare event. In addition, several drug-sensitive isolates from urinary tract infections were shown to be competent recipients of drug resistance determinants. From these data, it appears that the transferable drug resistance observed was mediated by R factors.